Anaesthesia consent considerations in children and young people. Issue 11 (November 2021) - Casby, Caoimhe; Lyons, Barry
Abstract: The law relating to consent for medical interventions in children is complex. Children, when they are old or mature enough, can consent for themselves. When they are unable to do so, consent must be sought from someone with parental responsibility. This article discusses consent, and its refusal, to medical interventions by children and adolescents.